THE DISCOVERY LEARNING MODEL FROM THE PERSPECTIVE OF HADITH - Ash shifa; Syabuddin (Jurnal Ikhtibar Nusantara, 2026)
This study discusses the Discovery Learning model from an Islamic perspective, emphasizing its relevance to the development of students’ potential. Discovery Learning is a student-centered learning model that highlights the process of concept discovery through investigation, observation, and direct experience, thereby fostering critical thinking, creativity, and independence. This research employs a qualitative approach with a library research method in a descriptive-analytical form. The findings indicate that Discovery Learning has a philosophical foundation aligned with the principles of Islamic education, as reflected in the Qur’an and Hadith, which encourage thinking, researching, and seeking knowledge as acts of worship. For instance, QS. Al-‘Alaq verses 1–5 emphasize the importance of reading and acquiring knowledge, which is in line with the principles of discovery learning. From an Islamic perspective, this model supports the development of human potential in the form of intellect and curiosity, while also cultivating critical thinking, responsibility, and independence. Discovery Learning also offers advantages such as enhancing problem-solving skills, fostering independence, and promoting active learning. Nevertheless, it also presents limitations, including requiring more time, demanding teacher readiness, and necessitating a resource-rich learning environment. Thus, Discovery Learning can serve as a strategic alternative for improving the quality of education, not only focusing on cognitive aspects but also integrating spiritual and moral values in accordance with Islamic teachings.